2013
DOI: 10.1093/cid/cit780
|View full text |Cite
|
Sign up to set email alerts
|

Active Tuberculosis and Venous Thromboembolism: Association According to International Classification of Diseases, Ninth Revision Hospital Discharge Diagnosis Codes

Abstract: Tuberculosis must be considered as a pertinent risk factor for VTE and should be included in thromboembolism risk evaluation similar to any acute and severe infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 39 publications
(40 reference statements)
3
65
1
1
Order By: Relevance
“…Finally, the main striking finding of this study is the association of TB diagnosis with venous thromboembolic events (VTE), documented in 31% of cases. In a recent study, TB was found to be an independent risk factor for VTE with a VTE prevalence of 2% among patients with active TB [10]. The much higher prevalence in our study could be explained by the conjunction of two pro-inflammatory states (i.e.…”
contrasting
confidence: 40%
“…Finally, the main striking finding of this study is the association of TB diagnosis with venous thromboembolic events (VTE), documented in 31% of cases. In a recent study, TB was found to be an independent risk factor for VTE with a VTE prevalence of 2% among patients with active TB [10]. The much higher prevalence in our study could be explained by the conjunction of two pro-inflammatory states (i.e.…”
contrasting
confidence: 40%
“…6,7 There are very few reports of thrombotic complications among children with TB, possibly due to under-reporting. 3,4 This type of rare but serious complication can further increase the morbidity and mortality associated with TB in young children; 8 as such, clinicians should keep a high index of suspicion of DVT. To the best of the authors' knowledge, this is the first reported case of childhood abdominal TB with DVT and intracranial sinus thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The risk of VTE also depends on the treatment of specific coinfections frequently observed in these patients, such as tuberculosis, Cytomegalovirus, and HCV, which contribute to the inflammatory e nvironment during cART. 9 Increasing age is one of the main acquired risk factors for VTE. 1 Interestingly, the profile of HIVassociated changes in markers of inflammation and coagulation are very similar to those reported with ageing and increased frailty in the general population (including a decline in endothelial nitric oxide production; increased platelet acti vation; and increased levels of ddimer, factors VIII, IX, and XI, fibrinogen, IL6, and von Willebrand factor).…”
Section: Correspondencementioning
confidence: 99%